Exploring the Medical Screening Process of Fire Officer 1 Applicants in the Bureau of Fire Protection in Region 5 - Caceres, Dan Romulo; Macabeo, Manny (JPAIR Multidisciplinary Research, 2025)
Republic Act No. 9263 sought to enhance the professionalism and effectiveness of the BFP and BJMP by ensuring that their personnel are well-qualified, adequately compensated, and provided with opportunities for career advancement. The study aims to explore the medical screening process experience of Fire Officer 1 applicant in the Bureau of Fire Protection Regional Office V and identify potential problems in terms of medical requirements and implementation. The research study utilizes a qualitative method, including documentary and thematic analysis. The study’s respondents are the recently hired FO1s and medical staff of the BFP Region 5. The findings revealed inadequate medical test requirements and medical procedures in the medical screening process. The potential problems regarding medical requirements are errors in medical evaluation, the authenticity of medical results, and issues in acquiring clearances. In terms of medical implementation, requiring various medical clearances, and misplaced medical results are its problems. As a result, the medical screening process is hindered by both insufficient test requirements and flawed procedures. This leads to inaccurate evaluations, questionable result authenticity, difficulties obtaining clearances, and logistical implementation issues.